REFORMS BEING IMPLEMENTED IN THE NEW UZBEKISTAN UNDER THE LEADERSHIP AND INITIATIVE OF PRESIDENT SH. M. MIRZIYOYEV - Bobokulova Khurshida Erkinovna; Toshpulatova Durdona Orzimurod qizi (The Conference Hub, 2025)
This scientific article deeply analyzes the large-scale reforms in the socio-political, economic and judicial systems of New Uzbekistan, which are being implemented under the leadership and initiative of the esteemed President of Uzbekistan, Sh. M. Mirziyoyev. The study highlights the work carried out on the basis of the "Action Strategy" for 2017-2021 and the "Development Strategy" for 2022-2026. The article highlights the expansion of market mechanisms, structural reforms and strengthening of principles in the education and health care systems. It also highlights the impact of these changes on the well-being of society and the individual and the importance of these processes.
Keywords: president, ongoing reforms, socio-political changes, public administration, citizens, opportunities, standard of living of the population